Dengue and SARS-CoV-2 co-circulation and overlapping infections in hospitalized patients - Santos, Thayza M. I. L.; Versiani, Alice F.; Campos, Guilherme R. F.; Moraes, Marilia M.; Parra, Maisa C. P.; Mistrao, Natalia F. B.; Negri, Andreia F.; Bagno, Flavia F.; Galves, Marina G.; Moreno, Camila M.; Da Fonseca, Flavio G.; Estofolete, Cassia F.; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Since its emergence in 2019, coronavirus disease (COVID-19) has spread worldwide and consumed public health resources. However, the world still has to address the burdens of other infectious diseases that continue to thrive. Countries in the tropics and neotropics, including Brazil, are affected by annual, cyclic dengue epidemics. Little is known about the impact of subsequent infections between DENV and SARS-CoV-2. Our study was performed on 400 serum samples collected from laboratory-confirmed COVID-19 patients between January and June 2021, months historically known for DENV outbreaks in Brazil. The samples were tested by serology and molecular assays for the presence of DENV and other arboviruses. While no DENV PCR results were detected, 6% were DENV IgM-positive, and 0.25% were DENV NS1-positive according to ELISA. IgM antibodies were isolated by chromatography, and 62.5% of the samples were positive for neutralizing antibodies (FRNT80) against DENV IgM, suggesting a recent infection. We also observed increased IL-10, TNF-α, and IL-1β levels in patients with overlapping SARS-CoV-2/DENV infections. Intriguingly, diabetes was the only relevant comorbidity (p=0.046). High rates of hospitalization (94.9%) and mortality (50%) were found, with a significant increase in invasive mechanical ventilatory support (86.96%) in SARS-CoV-2/DENV- infected patients, suggesting an impact on patient clinical outcomes. When analyzing previous exposure to DENV, secondary dengue patients infected with SARS-CoV-2 more frequently presented with dyspnea and respiratory distress, longer hospital and intensive care unit (ICU) stays (4 and 20.29 days, respectively) and a higher mortality rate (60%). However, a greater proportion of patients with primary DENV infection had fever and cough than patients with secondary dengue (87.50% vs. 33.33%, p=0.027 for fever). Our data demonstrate that differentiating between the two diseases is a great concern for tropical countries and should be explored to improve patient management.